Bio-orthogonal conjugation and enzymatically triggered release of proteins within multi-layered hydrogels. (1st July 2017) - Guo, Chen; Kim, Heejae; Ovadia, Elisa M.; Mourafetis, Christine M.; Yang, Mingrui; Chen, Wilfred; Kloxin, April M.
Graphical abstract: Abstract: Hydrogels are facile architectures for the controlled presentation of proteins with far-reaching applications, from fundamental biological studies in three-dimensional culture to new regenerative medicine and therapeutic delivery strategies. Here, we demonstrate a versatile approach for spatially-defined presentation of engineered proteins within hydrogels through i) immobilization using bio-orthogonal strain-promoted alkyne-azide click chemistry and ii) dynamic protease-driven protein release using exogenously applied enzyme. Model fluorescent proteins were expressed using nonsense codon replacement to incorporate azide-containing unnatural amino acids in a site-specific manner toward maintaining protein activity: here, cyan fluorescent protein (AzCFP), mCherry fluorescent protein (AzmCh), and mCh decorated with a thrombin cut-site. (AzTMBmCh). Eight-arm poly(ethylene glycol) (PEG) was modified with dibenzylcyclooctyne (DBCO) groups and reacted with azide functionalized PEG in aqueous solution for rapid formation of hydrogels. Azide functionalized full-length fluorescent proteins were successfully incorporated into the hydrogel network by reaction with PEG-DBCO prior to gel formation. Temporal release and removal of select proteins (AzTMBmCh) was triggered with the application of thrombin and monitored in real-time with confocal microscopy, providing a responsive handle for controlling matrix properties. Hydrogels with regions of different protein compositions were created using a layering technique with thicknesses of hundreds of micrometers, affording opportunities for the creation of complex geometries on size scales relevant for controlling cellular microenvironments. Statement of Significance: Controlling protein presentation within biomaterials is important for modulating interactions with biological systems. For example, native tissues are composed of subunits with different matrix compositions (proteins, stiffness) that dynamically interact with cells, influencing function and fate. Toward mimicking such temporally-regulated and spatially-defined microenvironments, we utilize bio-orthogonal click chemistry and protein engineering to create hydrogels with distinct regions of proteins and modify them over time. Through nonsense codon replacement, we site-specifically functionalize large proteins with i) azides for covalent conjugation and ii) an enzymatic cleavage site for user-defined release from hydrogels. Our results exemplify not only the ability to create unique bio-functionalized hydrogels with controlled mechanical properties, but also the potential for creating interesting interfaces for cell culture and tissue engineering applications.